Novel dam-like effect based on piezoelectric energy conversion for drug sustained release of drug-loaded TiO2 @ BaTiO3 coaxial nanotube coating. Issue 12 (15th June 2021) - Wu, Cong; Wei, Xinghui; Zhao, Kang; Jiang, Junyi; Jiao, Mengzhen; Cheng, Junhua; Tang, Zhen; Guo, Zheng; Tang, Yufei
Abstract: Nanotube coatings on titanium surfaces have favorable biocompatibility and structures and are widely used in local drug delivery. However, when a drug freely diffuses out of a nanotube, it leads to an explosive release, making the duration of action extremely short. In this study, a high concentration of vancomycin hydrochloride region similar to a dam was formed on a nanotube coating surface by exploiting the attraction of the electric charge generated by the energy conversion of the piezoelectric effect to vancomycin hydrochloride. The "dam" not only reduces the diffusion rate of vancomycin hydrochloride inside the nanotube into the dam and the diffusion rate of the dam to the outside but also forms a high concentration of vancomycin hydrochloride action region. The free diffusion rate of vancomycin hydrochloride loaded on the TiO2 @ BaTiO3 coaxial nanotubes was reduced by the piezoelectric effect, and the cumulative release of vancomycin hydrochloride for 7 days is reduced by 54.8%. The polarized vancomycin-containing coaxial nanotube coating has a long-lasting antibacterial effect on Staphylococcus aureus . The TiO2 @ BaTiO3 coaxial nanotubes loaded with vancomycin hydrochloride coating with piezoelectric properties has potential application value in controlled drug delivery.